HOW GREEN THE HUMAN RESOURCE MANAGERS ARE?: PERSPECTIVES OF HR MANAGERS FROM A CLIMATE CHANGE VICTIM REGION - UDDIN, MAEEN (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
Current environmental crises make us vulnerable to disasters and tragedies. With environmental problems mounting up, unless immediately addressed with care, we are surely to be doomed. The objective of this qualitative study is to figure out the level of concern as well as understanding that the organizations have on green aspect of Human Resource Management (Green HRM) and also to get an idea about the real implications of green HRM practices. The aim is to interview HR managers from different organizations, manufacturing in nature as Green concept mostly affect this particular area the most and to get a clear picture about their perspectives on Green HRM practices. HR managers from 10 organizations were interviewed, where the respondents were asked questions for 45-60 minutes by a team of 4-5 members. The questions asked during the interview were probed and found that most of the organizations although seemed well informed about the importance of going green concept, but only a few practice it through their actions in day to day HRM functions. The prime limitation is the size of the sample, an extensive study could be carried out in future. The signal from this study is very evident that organizations are familiar with green concepts, but they lack the motivation and top management support as well as monitoring to put this green concept into action for passing on a sustainable, and healthier environment for the generations to come. This study provides an extensive review of literature where the Green HRM practicality examination was needed to be applied into a climate change victim region and the paper successfully finds out the extent of HR managers perspectives and their actions and also provides guidelines to the manufacturing industry and policy makers.